TECHNICAL VOCATIONAL EDUCATION AND TRAINING IN SOUTH-SOUTH, NIGERIA: A VERITABLE TOOL FOR SUSTAINABLE ECONOMIC GROWTH - Nwojiewho, Isaac (International Journal of Research -GRANTHAALAYAH, 2017)
This study examined how technical vocational education and training (TVET) in the South-South Nigeria could serve as a tool for sustainable economic growth. Strategies for sustainable economic growth within the Niger Delta region and challenges of TVET in this region were discussed. This paper stressed the need for a proper conducive learning environment if TVET objectives will be achieved. From the study, it was found that in South-South region the TVET systems, their strategies and polices have not been aligned sufficiently with the regional economic needs and labour market demands. The study gathered that due to urgent needs for skilled manpower in this region, the State Governments and the Niger Delta Development Commission (NDDC) have established many skills acquisition centers that produce manpower for oil and gas industry amongst others. Based on the findings, the following recommendations were made: industries must make TVET a stronger focus of their economic and human resources development; TVET should be remolded to enhance the demand of our industry; industries should be involved in all designs and implementation of TVET programmes, there should be a cooperation between tertiary institutions, Government and industry; finally the teachers and instructors should given be in-service training regularly.